Socio-economic Damages caused by the 2014 Flood in Punjab Province, Pakistan: Socio-Economic Damages caused by the 2014 Flood in Punjab - Rahman, Ghani; Rahman, Atta-ur-; Anwar, Muhammad Mushahid; Ahmed, Mehtab; Ashraf, Humayun; Zafar, Umayya (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2017)
This study aimed at analyzing impact of the 2014 flood on socio-economic and infrastructural aspects in Punjab province, Pakistan. During the month of September 2014, heavy and prolonged monsoon rainfall was recorded over the north and north-eastern parts of Pakistan which fall in the catchment area of Indus river system. As a consequence, it overflowed natural levees in almost all the rivers flowing through the Punjab province and resulted in a devastating flood. A similar flood in 2010 had brought massive damages in 16 districts of Punjab province; over the past, the province has frequently suffered with such devastating flood events. In order to achieve the study objectives, the relevant data were collected from Pakistan Meteorology Department and Provincial Disaster Management Authority Punjab, and the same were spatially analyzed in the geographic information system (GIS) environment. The analysis revealed that during September 2014, high level of flood discharges were recorded at several gauging stations of Chenab and Jhelum rivers. As a result, this massive flood water overflowed the agricultural lands, destroyed standing crops, and damaged houses and other valuable infrastructures. In addition to heavy damages to agricultural and housing sector, it also incurred loss of 185 precious human lives and displaced 2.3 million people. This study revealed that during the 2014 flood in Punjab province, Jhang was the most severely affected district in terms of agricultural damages, whereas Sialkot district experienced maximum human casualties.